2017
DOI: 10.1038/ncomms15887
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the Tibetan Plateau during the Neogene

Abstract: The appearance of detritus shed from mountain ranges along the northern margin of the Tibetan Plateau heralds the Cenozoic development of high topography. Current estimates of the age of the basal conglomerate in the Qaidam basin place this event in Paleocene-Eocene. Here we present new magnetostratigraphy and mammalian biostratigraphy that refine the onset of basin fill to ∼25.5 Myr and reveal that sediment accumulated continuously until ∼4.8 Myr. Sediment provenance implies a sustained source in the East Kun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
255
2
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(286 citation statements)
references
References 56 publications
16
255
2
7
Order By: Relevance
“…It is consistent with thermochronological data along the mountain ranges in the southern margin of the Qilian Shan, which has undergone a phase of accelerated exhumation since the early‐middle Miocene (Pang et al, ; Zhuang et al, ). It is also supported by provenance analyses for the Qaidam Basin, which indicate that early Cenozoic sediments in the northern Qaidam Basin were shed from the Kunlun Shan rather than the southern Qilian Shan, and provenance change occurred during early‐middle Miocene (Bush et al, ; W. Wang, Zheng, Zhang, et al, ). While Lu et al () suggest that Bush et al () may misidentify the underlying Cretaceous Quanyagou formation as the lower part of the Lulehe formation such that produce improper conclusions, they concluded that the Lulehe formation is characterized by proximal alluvial fan deposits that originated from the northern Qaidam Basin and the southern Qilian Shan based on evidence of sedimentology, facies analysis, and seismic reflection profiles (e.g., F. Cheng et al, ; Lu et al, ; Yin et al, ).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…It is consistent with thermochronological data along the mountain ranges in the southern margin of the Qilian Shan, which has undergone a phase of accelerated exhumation since the early‐middle Miocene (Pang et al, ; Zhuang et al, ). It is also supported by provenance analyses for the Qaidam Basin, which indicate that early Cenozoic sediments in the northern Qaidam Basin were shed from the Kunlun Shan rather than the southern Qilian Shan, and provenance change occurred during early‐middle Miocene (Bush et al, ; W. Wang, Zheng, Zhang, et al, ). While Lu et al () suggest that Bush et al () may misidentify the underlying Cretaceous Quanyagou formation as the lower part of the Lulehe formation such that produce improper conclusions, they concluded that the Lulehe formation is characterized by proximal alluvial fan deposits that originated from the northern Qaidam Basin and the southern Qilian Shan based on evidence of sedimentology, facies analysis, and seismic reflection profiles (e.g., F. Cheng et al, ; Lu et al, ; Yin et al, ).…”
Section: Discussionmentioning
confidence: 73%
“…This is supported by thermochronological data in the Qimen Tagh (Jolivet et al, ; D. Liu, Li, et al, ; Y. Wang et al, ), eastern Kunlun Shan (Clark et al, ; Mock et al, ; F. Wang, Shi, et al, ), and northern margin of the Qaidam Basin (He et al, ; Jolivet et al, ), and estimation on the sediments preserved in the Qaidam Basin and materials eroded in the surrounding drainage area (Cheng et al, ). However, recent published magnetostratigraphy and mammalian biostratigraphy refine the onset of basin fill in the Qaidam Basin to ~25.5 Ma and reveal that the detritus shed from the southern Qilian Shan occurred at ~12 Ma, suggesting that the deformation in the southern Qilian Shan is significantly later than previously estimated (W. Wang, Zheng, Zhang, et al, ). It is consistent with thermochronological data along the mountain ranges in the southern margin of the Qilian Shan, which has undergone a phase of accelerated exhumation since the early‐middle Miocene (Pang et al, ; Zhuang et al, ).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This petroliferous basin is filled with as much as ~14 km of Cenozoic clastic sedimentary rocks, that preserves an exceptional record of the intraplate response to the India‐Asia collision and postcollision convergence (Meng & Fang, ; Métivier et al, ; Meyer et al, ; Molnar & Tapponnier, ; Rieser et al, ; Xia et al, ; Yin, Dang, Wang, et al, ; Yin, Dang, Zhang, et al, ; Yin et al, ). Investigating the nature of these strata provides constraints on the topographic evolution of northern Tibet and the overall pattern of the Cenozoic plateau growth (Bush et al, ; F. Cheng, Fu, et al, ; F Cheng, Guo, et al, ; F. Cheng, Jolivet, et al, ; Fang et al, ; Ji et al, ; W Wang, Zheng, et al, ; Zhuang et al, ). Nonetheless, the depositional age of these Cenozoic strata remains highly debated.…”
Section: Introductionmentioning
confidence: 99%